Effect of complementary irrigation and organic fertilizers on tree growth and flowering of Olive tree( khodeiry variety) - عباس خلود; جرجس مخول; فيصل وجيه دواي; محمد نداف (Latakia University Journal -Biological Sciences Series, 2023)
نفذت التجربة خلال المواسم 2020، 2021، 2022 في بستان زيتون في قرية رويسة الحرش التابعة لمحافظة اللاذقية، على صنف الزيتون "الخضيري" بعمر 30 سنة، بهدف دراسة تأثير الري التكميلي والتسميد العضوي في النمو والإزهار والعقد. استخدم السماد العضوي 5 ، 7 كغ في شهر تشرين الثاني، أما ماء الري استخدم بثلاث مواعيد وبمعدل ماء ري ثابت 800 ليتر شجرة الرية. حُسب متوسط مساحة الورقة ،ومتوسط الزيادة في أطوال الطرود ،وعدد العناقيد الزهرية على الفرع وعدد الأزهار في العنقود الزهري ونسبة الأزهار الخنثى، وقدرت حيوية حبوب اللقاح ونسبة العقد. من خلال نتائج التحليل الإحصائي لوحظ زيادة معنوية في جميع المؤشرات المدروسة عند تطبيق التسميد العضوي والري معاً؛ إذ أظهرت معاملة التسميد العضوي بمعدل 7 كغ وثلاث مرات ري زيادة معنوية في متوسط طول الطرود 23.63 سم، ومتوسط مساحة الورقة 6.323 سم2، وفي متوسط عدد العناقيد الزهرية 34.08 عنقود فرع، ومتوسط عدد الأزهار في العنقود 15.16 زهرة النورة، وفي نسبة الأزهار الخنثى 89.9%، وتفوقت المعاملتان (7كغ سماد عضوي+ 3 ريات) و (7 كغ سماد عضوي + ريتان) في النسبة المئوية لحبوب اللقاح الحية 92.63% ، 91.87% على التوالي، بينما حققت معاملة الشاهد أدنى القيم في جميع المؤشرات المدروسة. The experiment was carried out during three seasons 2020,2021,2022 on olive orchard in Lattakia Governorate on Khodeiry variety on 30 years old.The aim of studying the effect of of complementary irrigation and organic fertilizers on growth and the impact on flowering and set flower.it was used organic fertilizer 5,7 kg in November , while irrigation water were used in three times by 800 L/tree .In the same concentrations was measured average of ( leaf area, length of shoot, numbers of panicle , flowers of panicle ,proportion of hermaphrodite flowers, percentage of the aviable pollen and set fruit). Through the satatistical analysis showed a significant increase of all productive indicators when we use organic fertilizer and irrigation together . Treatment ( 7 kg organic fertilizer + 3 irrigation times ) showed significant increase in leaf area (6,323cm2) ,shoot length(23,63 cm) ,average of panicle (34,08 ) panicle ,average of flower on panicle (15.16) flower/ panicle , and proportion of hermaphrodite flowers (89,9)%. Whereas the percentage of the aviable pollen as average 92.63%, 91.87% (7 kg organic fertilizer + 3 times irrigation) and (7 kg organic fertilizer + 2 times irrigation). While control treatment recorded the minimum value in all the studied parameters.